2018
DOI: 10.1002/chem.201804515
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed C(sp3)−H Arylation of Primary Amines Using a Catalytic Alkyl Acetal to Form a Transient Directing Group

Abstract: C−H Functionalization of amines is a prominent challenge due to the strong complexation of amines to transition metal catalysts, and therefore typically requires derivatization at nitrogen with a directing group. Transient directing groups (TDGs) permit C−H functionalization in a single operation, without needing these additional steps for directing group installation and removal. Here we report a palladium catalyzed γ‐C−H arylation of amines using catalytic amounts of alkyl acetals as transient activators (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…[47] Very recently,B ull and co-workers reported the use of ac atalytic amount of stable alkyl acetal (L38 or L39) as at ransientl igand for the C(sp 3 )ÀHa rylationo fp rimary amines.They uncovered an unexpected formationofa7-membered palladacycle intermediate from activationo ft he e-C(sp 2 )ÀHb ond( Scheme24c). [48]…”
Section: )àHf Unctionalization Of Aminesmentioning
confidence: 99%
“…[47] Very recently,B ull and co-workers reported the use of ac atalytic amount of stable alkyl acetal (L38 or L39) as at ransientl igand for the C(sp 3 )ÀHa rylationo fp rimary amines.They uncovered an unexpected formationofa7-membered palladacycle intermediate from activationo ft he e-C(sp 2 )ÀHb ond( Scheme24c). [48]…”
Section: )àHf Unctionalization Of Aminesmentioning
confidence: 99%
“…We (Bull) demonstrated that bench stable alkyl acetals could be used as directing groups for the arylation of amines (Scheme 21c). 67 Under the reaction conditions, the acetal was cleaved to the aliphatic aldehyde which was proposed to form the directing group in the reaction. Several acetal directing groups were evaluated, and those bearing ether secondary binding sites proved promising.…”
Section: C(sp 3 )-H Functionalisation Of Aminesmentioning
confidence: 99%
“…Several advances in mechanistic understanding have been discussed in earlier sections of this review, including possible modes of catalyst deactivation, 67 and computational investigations of additional role of pyridone ligands. 72 There have also been several publications purely dealing with gaining a greater understanding of the mechanism underlying these impressive catalytic transformations, including uncovering potential roles of specific reagents, the mechanisms of C-H activation and the origins of regioselectivity for different substrates.…”
Section: Advances In Mechanistic Understandingmentioning
confidence: 99%
“…36 Instead of using aldehyde directly, Bull realized that simple a-oxylacetal can be applied as the directing aldehyde precursor in the g-arylation of aliphatic amines (Scheme 21). 37 Except for above examples where aldehydes (or their precursors) function in catalytic amount under the reaction conditions, stoichiometric amount of aldehyde, such as quinoline-8-carbaldehyde cat. 17 and salicylaldehyde cat.…”
Section: Coupling Reactionmentioning
confidence: 99%